40‐TFLOPS artificial intelligence processor with function‐safe programmable many‐cores for ISO26262 ASIL‐D. Issue 4 (2nd August 2020) - Han, Jinho; Choi, Minseok; Kwon, Youngsu
Abstract : The proposed AI processor architecture has high throughput for accelerating the neural network and reduces the external memory bandwidth required for processing the neural network. For achieving high throughput, the proposed super thread core (STC) includes 128 × 128 nano cores operating at the clock frequency of 1.2 GHz. The function‐safe architecture is proposed for a fault‐tolerance system such as an electronics system for autonomous cars. The general‐purpose processor (GPP) core is integrated with STC for controlling the STC and processing the AI algorithm. It has a self‐recovering cache and dynamic lockstep function. The function‐safe design has proved the fault performance has ASIL D of ISO26262 standard fault tolerance levels. Therefore, the entire AI processor is fabricated via the 28‐nm CMOS process as a prototype chip. Its peak computing performance is 40 TFLOPS at 1.2 GHz with the supply voltage of 1.1 V. The measured energy efficiency is 1.3 TOPS/W. A GPP for control with a function‐safe design can have ISO26262 ASIL‐D with the single‐point fault‐tolerance rate of 99.64%.